The Mediterranean lifestyle (MEDLIFE) index and metabolic syndrome in a non-Mediterranean working population - Hershey, Maria S.; Sotos-Prieto, Mercedes; Ruiz-Canela, Miguel; Christophi, Costas A.; Moffatt, Steven M.; Martínez-González, Miguel Ángel; Kales, Stefanos N. (My University, 2021)
Background & aims: The Mediterranean lifestyle (MEDLIFE), as an overall lifestyle pattern, may be associated with a lower prevalence of metabolic syndrome. We assessed the association of a validated MEDLIFE index with metabolic syndrome and its components in a non-Mediterranean working population. Methods: A cross-sectional analysis was conducted at baseline among 249 US career firefighters in Feeding America's Bravest 2016–2018. The MEDLIFE index consisted of 26 items on food consumption, dietary habits, physical activity, rest, and social interactions that scored 0 or 1 point. Thus, total scores could range from 0 to 26 points. Multivariable logistic regression models were used to determine the associations across tertiles of MEDLIFE adherence with metabolic syndrome and each of its individual components. Multivariable linear models further assessed each component as a continuous outcome. Results: The prevalence of metabolic syndrome was 17.7%. Participants with higher MEDLIFE adherence (T3: 11–17 points) had 71% lower odds of having metabolic syndrome compared to those with lower MEDLIFE adherence (T1: 2–7 points) (OR = 0.29; 95%CI: 0.10 to 0.90, p for trend = 0.04). Furthermore, significant inverse associations were found for T3 versus T1 on abdominal obesity (OR = 0.42; 95%CI: 0.18 to 0.99, p for trend = 0.07) and hypertriglyceridemia (OR = 0.24; 95%CI: 0.09 to 0.63, p for trend = 0.002). Significant inverse associations for continuous outcomes included total-cholesterol (total-c), low-density lipoprotein (LDL) cholesterol, and total-c:high-density lipoprotein (HDL) cholesterol (p for trend <0.05). Conclusion: Higher adherence to traditional Mediterranean lifestyle habits, as measured by a comprehensive MEDLIFE index, was associated with a lower prevalence of metabolic syndrome and a more favorable cardiometabolic profile in a non-Mediterranean working population. Future studies employing the MEDLIFE index in other populations are warranted to support this hypothesis.
Keywords: Metabolic syndrome; Lifestyle; Cardiovascular disease; Type 2 diabetes mellitus; Mediterranean diet